2006
DOI: 10.1063/1.2202005
|View full text |Cite
|
Sign up to set email alerts
|

Detecting clandestine material with nuclear resonance fluorescence

Abstract: We study the performance of a class of interrogation systems that exploit nuclear resonance fluorescence (NRF) to detect specific isotopes. In these systems the presence of a particular nuclide is inferred by observing the preferential attenuation of photons that strongly excite an electromagnetic transition in that nuclide. Estimates for the false positive/negative error rates, radiological dose, and detection sensitivity associated with discovering clandestine material embedded in cargo are presented. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 137 publications
(69 citation statements)
references
References 13 publications
0
66
0
1
Order By: Relevance
“…The results of the modeling effort to understand the basic detection limits of NRF systems have been submitted for publication [3] and are summarized here. Fig.…”
Section: Results/technical Outcomementioning
confidence: 99%
“…The results of the modeling effort to understand the basic detection limits of NRF systems have been submitted for publication [3] and are summarized here. Fig.…”
Section: Results/technical Outcomementioning
confidence: 99%
“…Detecting a large amount of single isotopes such as weapons-grade Uranium hidden in a cargo can be conducted by using an electron accelerator of smaller beam current and a single NaI detector combined with a notch filter as proposed in a previous study. 6) In the present study, we have chosen the germanium detector system because of its high energy resolution. As alternative methods, utilization of NaI, BGO, and LaBr 3 scintillators can be suggested and its consideration is a further subject.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that the notch can be refilled by parasitic scattering processes [9], as illustrated in Fig. 1(b).…”
Section: B Nrf Detection and Notch Refillingmentioning
confidence: 99%